The Construction of Reality: Bashar Al Assad's Resignation from the Presidency of Syria in Al Jazeera Arabic Media Discourse - Rahmi, Deri; Hidayatullah, Achmad Diny (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study uses Norman Fairclough's Critical Discourse Analysis approach to analyze how Al Jazeera Arabic media shapes the construction of reality regarding the fall of Bashar al-Assad from the Syrian presidency. This study uses two data types in different formats: online news articles and videos from Al Jazeera Arabic's YouTube channel. The use of these two media formats represents a novelty in discourse studies as it expands the scope of analysis to include variations in text form and medium. The research was conducted using a qualitative approach and Fairclough's three-dimensional discourse analysis technique, namely the dimensions of text, discourse practice, and social practice. The results of the analysis show that both data sets use ideological and symbolic language to frame the Bashar al-Assad regime as a repressive actor and the opposition group as a legitimate force of the people. In discourse practice, the media constructs narratives with production strategies involving symbolism, emotional narratives, and intertextual support. Socially, the discourse constructed reflects an alignment with the narrative of the people's revolution and rejects the legitimacy of authoritarian power. Thus, the media does not merely reflect reality but actively shapes it through its choice of narratives and discourse structures.